Plasmonic imaging the catalysis of single graphene sheets – The edge effect. (May 2022) - Chen, Shan; Yin, Congcong; Huang, Zongxiong; Chen, Junyan; Zheng, Yuhao; Chen, Jinghu; Yang, Shuangli; Su, Yuwen; Fang, Yimin
Abstract: Oxygen evolution reaction on a graphene sheet at negative potential is observed using surface plasmon resonance microscopy (SPRM). It is found that oxygen nanobubbles are evolved at negative potential due to the disproportion reaction of superoxide originated from the reduced dissolved oxygen, suggesting that graphene acts as a superoxide dismutase (SOD) mimic. SPRM reveals that the catalytic sites distribute at the edge and the bulk of graphene. Atomic force microscopy suggests that the active sites for bubble evolution in the bulk of graphene are located at internal edge originated from the holes in the graphene rather than the metal oxide residues remained on the graphene sheet. The metal oxide nanoparticles on the graphene sheet are not the direct active sites but also play important roles in promoting the catalysis by increasing the superoxide concentration through an electrocatalyzed Fenton reaction. This work also presents the first experimental evidence that the catalysis of graphene is generated from the edge effect in an in operando manner. The SPRM represents a universal tool to reveal the catalytic mechanism at microscale, and it is hoped to discover more exciting reactions on nanomaterials due to its label free feature, high sensitivity, and versatility to most of materials. Graphical abstract: Image 1 Highlights: Oxygen evolution reaction was observed at negative potential on a graphene sheet. This reaction was imaged at microscale in an in-operando manner. The edge of the graphene is the active site for oxygent nanobubbles evolution. The metal oxides on the graphene sheet are not the active sites, but promote this reaction.